2020
DOI: 10.3389/feart.2020.537800
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the 2017 Xinmo Catastrophic Landslide Considering Entrainment Effect

Abstract: The mass movement process of the 2017 Xinmo catastrophic landslide was simulated using the discreet element method (DEM). Field investigation indicates that the basal entrainment is a typical feature of this landslide. Hence, the entrained colluvium on the sliding path is considered in the DEM model. According to the terrain elevation data before and after sliding, the slope geometry is divided into three parts: sliding bed, sliding body, and colluvium on the path. The blocks are generated in MATLAB and a fill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The latter is dropping sharply below the secondary scarp at the Assapaat frozen debris avalanche as shown by our volume calculation. Also, Chen et al (2020) showed through numerical modelling of the 2017 Xinmo landslide that entrainment of dry material on the slope leads to more frictional energy consumption and a reduction of landslide mobility. We therefore conclude that entrainment of the large dry permafrozen volume inside the secondary scarp together with the low slope gradient consumed a large fraction of the kinetic energy of the frozen debris avalanche.…”
Section: Entrainment On the Permafrozen Slopementioning
confidence: 99%
“…The latter is dropping sharply below the secondary scarp at the Assapaat frozen debris avalanche as shown by our volume calculation. Also, Chen et al (2020) showed through numerical modelling of the 2017 Xinmo landslide that entrainment of dry material on the slope leads to more frictional energy consumption and a reduction of landslide mobility. We therefore conclude that entrainment of the large dry permafrozen volume inside the secondary scarp together with the low slope gradient consumed a large fraction of the kinetic energy of the frozen debris avalanche.…”
Section: Entrainment On the Permafrozen Slopementioning
confidence: 99%
“…Luchedu landslide is on the eastern edge of the Qinghai Tibet Plateau. A few similar severe slope disasters occurred there, including the Lannigou landslide and Yigong landslide [1][2][3][4], all of which evolved from rock slides or rock falls at the beginning to a disaster chain event of dam building, river blocking, and collapse. Through field investigation, the Luchdu landslide had the characteristics of high speed and fluidization and was full of detritus, feasible to be categorized as a rock avalanches or debris avalanches.…”
Section: Introductionmentioning
confidence: 99%
“…Landslide dam is one of the most devastating natural disasters worldwide, especially in the mountainous areas of Southwest China. As a result of earthquake, rainfall, snow melting and other factors, soil or rock slopes slide and block the valley or river, forming a landslide dam (Costa and Schuster, 1988;Korup, 2002;Dunning et al, 2007;Huang, 2009;Chen et al, 2020;Zhou et al, 2020). As a natural dam, the landslide dam body consists of loose and un-compacted materials, and it is easy to burst in a very short time, resulting in a large number of floods, threatening the safety of life and property in up-and-down stream districts (Zhou et al, 2013;Fan et al, 2014;Zhou et al, 2016;Choi et al, 2018;Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%